Global sourcing practices: a framework to improve sourcing strategy implementation - Mohamad, Marini Nurbanum Binti (Cranfield University, 2009)
The aim of the research reported in this thesis is to gain understanding of global sourcing practices of companies in the UK and to develop a framework to improve sourcing strategy implementation. This research was conducted by carrying out literature review, analysis of case studies through semi-structured interviews, analysis of an online-based survey, development of a global sourcing framework, feedback process and finally the refinement of the framework. The global sourcing practices, in terms of eight critical success factors, which were identified through literature, was investigated through case studies. This research also provides insights into how critical certain factors are to the effectiveness of the company‟s sourcing strategy and how broadly were those factors actually implemented. The gaps between the perceived importance of global sourcing practices and the actual implementation were explored through survey. The information gathered from the literature, case studies and survey provided the input to develop a global sourcing framework. As more and more studies create awareness of the critical success factors that are important for implementing a global sourcing strategy, there is a need for a framework to be developed to help a company identify areas where they can improve in terms of implementation of the sourcing strategy. The global sourcing framework was developed to assess the current sourcing level of companies, providing guidance for companies to identify the areas for improvement in their approach to global sourcing and helping companies determine where they need to be in terms of the global sourcing strategy and having it aligned with their corporate strategy. The framework has been validated and found to be feasible, usable and useful to improve a company‟s sourcing strategy.